G2P-DBSCAN: estratégia de particionamento de dados e de processamento distribuído fazer DBSCAN com MapReduce. - Araújo Neto, Antônio Cavalcante (2016)
Clustering is a data mining technique that brings together elements of a data set such so that the elements of a same group are more similar to each other than to those from other groups. This thesis studied the problem of processing the clustering based on density DBSCAN algorithm distributedly through the MapReduce paradigm. In the distributed processing it is important that the partitions are processed have approximately the same size, provided that the total of the processing time is limited by the time the node with a larger amount of data leads to complete the computation of data assigned to it. For this reason we also propose a data set partitioning strategy called G2P, which aims to distribute the data set in a balanced manner between partitions and takes into account the characteristics of DBSCAN algorithm. More Specifically, the G2P strategy uses grid and graph structures to assist in the division of space low density regions. Distributed DBSCAN the algorithm is done processing MapReduce two stages and an intermediate phase that identifies groupings that can were divided into more than one partition, called candidates from merging. The first MapReduce phase applies the algorithm DSBCAN the partitions individually. The second and checks correcting, if necessary, merge candidate clusters. Experiments using data sets demonstrate that true G2P-DBSCAN strategy overcomes the baseline adopted in all the scenarios, both at runtime and quality of obtained partitions.